Rocking the boat — nursing students' stories of moral courage: A qualitative descriptive study. (July 2016) - Bickhoff, Laurie; Levett-Jones, Tracy; Sinclair, Peter M.
Abstract: Aim: This paper profiles a qualitative study that examined how undergraduate nursing students demonstrate moral courage when confronted with clinical situations that negatively impact the quality of patient care and/or patient experience and the factors that encouraged or inhibited their willingness to speak up when they identified poor practice. Background: Clinical placements are an essential component of nursing programmes. However, placements are a reported source of stress for students, with many witnessing, or feeling compelled to participate in, poor practice. In these instances, nursing students require the moral courage to raise concerns in order to protect patient safety and dignity. Methods: This was a qualitative descriptive study. Nine nursing students and one nursing graduate from one semi-metropolitan university in Australia were interviewed and the data were thematically analysed. Findings: Four key themes emerged: (1) patient advocate identity, which had two sub-themes of knowing one's own moral code and previous life experiences; (2) consequences to the patient and to the participant; (3) the impact of key individuals; and (4) picking your battles. Conclusion: This study demonstrates the importance of undergraduate nursing students identifying as patient advocates, the multitude of consequences students face when questioning the practice of a registered nurse, and the influence supervising nurses and clinical facilitators have on a student's decisions to intervene to protect patient safety. Further research is required to examine the factors, both intrinsic and extrinsic, that influence nursing students' moral courage and their decisions to intervene when poor practice is witnessed. Highlights: Nursing students require moral courage to question practices that jeopardise patient safety and dignity. Identifying as a patient advocate, understanding their moral code and other life experiences enhance students' moral courage. Students are cognisant any failure to intervene on their patients' behalf can have serious consequences. Mentors and clinical facilitators greatly impact a student's moral courage. Reflecting on their experiences, students report they will consider the risk to themselves before intervening again.